Spiritual well-being in breast cancer patients - Lestari, Hayatus Sa'adah Ayu; Sukartini, Tintin; Nihayati, Hanik Endang (Pediomaternal Nursing Journal, 2023)
Introduction: Breast cancer patients frequently experience spiritual discomfort due to the disease, its diagnosis, and its repercussions. When end-of-life patients' spiritual needs are not adequately served, they are forced to deal with an overall burden of daily distress and anxiety that affects their emotional and spiritual health. Several studies indicate that, when coping with cancer, people frequently turn to spirituality. Spirituality and religiosity have been associated with less depressive symptoms, enhancing well-being throughout cancer treatment and in cancer survivors. This study sought to characterize the spiritual health of breast cancer patients (religious well-being and existential well-being).Methods: A descriptive observational study design was used, and the population of this research was breast cancer patients at the public hospital. The sample total of this research was 104 respondents. The samples were chosen using non-probability sampling with a purposive sampling technique. Spiritual well-being as a variable was measured using the spiritual well-being scale. Data were then analyzed for categorization into less, enough, and good, expressed in frequencies and percentages. Results: The result of this research shows that good religious well-being with a total of 63 (60,6%) and existential well-being enough with a total of 56 (53,8%).Conclusions: This study demonstrates the responder's good existential and religious well-being categories. Palliative care can be added to medical therapies and programs to promote spiritual well-being, such as spiritual counseling, meditation, and dhikr therapy, which can be helpful for patients with breast cancer.Keywords: breast cancer; existential well-being; religious well-being; spiritual well-being